Perspektif Imam Al-Ghazali dan Ibn Taimiyah dalam Konsep Mekanisme Pasar dan Penetapan Harga terhadap Perekonomian Islam - Tambunan, Ria Tifanny; Hendra, Hendra (MODELING: Jurnal Program Studi PGMI, 2023)
The market has an ultimate level of economics. Islam considers the existence of a market mechanism to ensure that the market can move to be perfect. However, the fact is that there are often market distortions caused by the behavior of sellers. So Islam sees the importance of government intervention in price fixing. The benefit of this research is to examine the concept of market mechanisms and price fixing in the Islamic economy from the perspective of Imam Al-Ghazali and Ibn Taimiyah. The conceptual thinking of the market mechanism according to Imam Al-Ghazali, especially the factors that influence and based on this price theory on the market mechanism due to the law of supply and demand. Al-Ghazali explained that the government's duty is to oversee the market so that a fair and free market is created. According to Al-Ghazali, price fixing obtains maslahah hajiyyah, that is, everything that makes people feel comfortable when their needs are originally fulfilled. Ibn Taimiyah explained that prices are determined by supply and demand. There are problems where prices are increased due to imbalances and imbalances in the market mechanism, the government can intervene in prices. However, if prices rise/fall naturally in a normal situation, the government has no right at all to set prices.